THE CONCHOCELIS OF PORPHYRA HAITANENSIS (RHODOPHYTA) IS PROTECTED FROM HARMFUL UV RADIATION BY THE COVERING CALCAREOUS MATRIX(1) - Jiang, Hongxia (Journal of phycology, 2009)
© 2009 Phycological Society of America.